Connecting large-scale velocity and temperature bursts with small-scale intermittency in stratified turbulence. (7th September 2021) - Feraco, F.; Marino, R.; Primavera, L.; Pumir, A.; Mininni, P. D.; Rosenberg, D.; Pouquet, A.; Foldes, R.; Lévêque, E.; Camporeale, E.; Cerri, S. S.; Charuvil Asokan, H.; et al.
Abstract: Non-Gaussian statistics of large-scale fields are routinely observed in data from atmospheric and oceanic campaigns and global models. Recent direct numerical simulations (DNSs) showed that large-scale intermittency in stably stratified flows is due to the emergence of sporadic, extreme events in the form of bursts in the vertical velocity and the temperature. This phenomenon results from the interplay between waves and turbulent motions, affecting mixing. We provide evidence of the enhancement of the classical small-scale (or internal) intermittency due to the emergence of large-scale drafts, connecting large- and small-scale bursts. To this aim we analyze a large set of DNSs of the stably stratified Boussinesq equations over a wide range of values of the Froude number –1). The variation of the buoyancy field kurtosis with Fr is similar to (though with smaller values than) the kurtosis of the vertical velocity, both showing a non-monotonic trend. We present a mechanism for the generation of extreme vertical drafts and vorticity enhancements which follows from the exact equations for field gradients.